2021
DOI: 10.3390/su13169246
|View full text |Cite
|
Sign up to set email alerts
|

Can GIS Foster Conscious and Critical Learning in Geography? An Application from Students to a Real Case Included in the National Strategy for Inner Areas: Monti Dauni, Apulia (Italy)

Abstract: Digital technologies, the use of which has progressively increased over the last few years, could represent key tools in learning and active citizenship in development processes. In this sense, Geographical Information Systems (GIS) have gradually become an integral part of various disciplines and sectors. Even if the relevance and diffusion of GIS in the educational and pedagogical fields are increasing, their potential is still under-explored in the development of empowerment for participatory planning. Rega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…For example, Refs. [37][38][39][40] demonstrated that the use of Spatial Data Infrastructure (SDI) significantly enhanced students' sustainability consciousness. Additionally, in [39], the integration of geography and GIS through teaching experimentation, as applied to a real case study in the Apulia region (Monti Dauni Area) under the national strategy for inner areas, can be observed to understand how to use GIS as an active tool in education for sustainability as well as the awareness of the value of local resources and active citizenship.…”
Section: Innovative Approaches To Teaching Sdgsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Refs. [37][38][39][40] demonstrated that the use of Spatial Data Infrastructure (SDI) significantly enhanced students' sustainability consciousness. Additionally, in [39], the integration of geography and GIS through teaching experimentation, as applied to a real case study in the Apulia region (Monti Dauni Area) under the national strategy for inner areas, can be observed to understand how to use GIS as an active tool in education for sustainability as well as the awareness of the value of local resources and active citizenship.…”
Section: Innovative Approaches To Teaching Sdgsmentioning
confidence: 99%
“…Two experts in Social Science Education, who possess over a decade of teaching and research experience, reviewed the questionnaire and made minor modifications to the wording of the questions. To collect data, students completed the questionnaire online while maintaining anonymity [39]. The Google Form ® tool (Google LLC, Mountain View, CA, USA) [14] was employed for this purpose.…”
Section: Data Collectionmentioning
confidence: 99%